1977
DOI: 10.1073/pnas.74.10.4205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of galactose oxidase, with and without prior sialidase treatment, on the viability of erythrocytes in circulation.

Abstract: Previous studies have shown that sialidasetreated mammalian erythrocytes were rapidly eliminated from circulation. In contrast, chicken asialoerythrocytes remained fully viable. This investigation was undertaken to ascertain the reason for this difference in behavior as well as to determine the extent of the similarity of the physiological mechanism for the elimination from circulation of asialoglycoproteins and mammalian asialoerythrocytes. To that end, erythrocytes from dogs, rabbits, and chickens were each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The existence of unmasked galactosyl residues on the rabbit RBC was previously indicated by the reactivity of circulating rabbit erythrocytes to peanut agglutinin (27). These results were later confirmed by Bell et al (44), who further demonstrated that the major product obtained from intact rabbit RBC by galactosidase treatment was found to be D-galactose. These data may suggest that the GO-sensitive sites on the rabbit erythropoietic cells are terminal galactosyl, and not N-acetylgalactosaminyl, residues.…”
Section: Discussionsupporting
confidence: 76%
“…The existence of unmasked galactosyl residues on the rabbit RBC was previously indicated by the reactivity of circulating rabbit erythrocytes to peanut agglutinin (27). These results were later confirmed by Bell et al (44), who further demonstrated that the major product obtained from intact rabbit RBC by galactosidase treatment was found to be D-galactose. These data may suggest that the GO-sensitive sites on the rabbit erythropoietic cells are terminal galactosyl, and not N-acetylgalactosaminyl, residues.…”
Section: Discussionsupporting
confidence: 76%
“…One difference between the mouse and human erythrocyte surface which could be relevant to this point is the presence of antigens of the major histocompatibility complex on the surface of mouse cells in addition to blood group antigens [81]. The correlations which have been shown to exist between experimental modification of the terminal sialic acid or galactose/N-acetylgalactosaminyl residues of erythrocytes from several species and changes in blood clearance times [1,2,20,30,31,34,42] indicate the potential importance of such a modification. We have observed differences in the minor labeled proteins after lactoperoxidase catalyzed radioiodinization of mouse erythrocytes from different inbred strains 6, and these differences may be paralleled by differences in the surface glycoproteins, (ii) there is a relatively small number of glycoproteins incorporated into the mouse erythrocyte membrane, and artifactual or in vivo modification of these molecules produces a spectrum of products at various stages of modification.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of rat erythrocytes with galactose oxidase alone, followed by iv or ip transfusion, results in their sequestration in both the liver and spleen (Table II), implicating terminal galactose or N-acetylgalactosamine residues in rat RBC that are susceptible to oxidation with a concomitant loss of viability [22]. Table I11 shows the distribution of radioactivity in the parenchymal and nonparenchymal cells of liver, 24 hr post ip transfusion of aRBC.…”
Section: R Es U Lts Effects Of Excess Na251cr04 Label On Viability Ofmentioning
confidence: 98%